The archaeological context of the Palaeohispanic Southwestern script (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
The territory involved by the evidence of Southwest scripts is divided into three main areas that show different characteristics regarding the density and quality of their archaeological contexts. The South of Portugal, the region which has provided the highest number of epigraphs, shows a limited number of well-documented contexts for the large amount of stone stelae found from the 18th century; Western Andalusia is characterized by the extreme scarcity of testimonies, in contrast to other evidence, such as the importance of Phoenician epigraphy or the strength of the Early Iron Age societies in this area; the region of Extremadura shows a variety of situations in a background that, thanks to recent researches, has become something more dynamic. The study of these three areas allows us to make a general proposal for the chronology of the Southwest Script, as well as to raise some notes regarding its social and cultural uses.
Keywords: Paleohispanic epigraphy; Portugal; Western Andalusia; Extremadura; Archaeological contexts; Iron Age.